2018
DOI: 10.1002/pc.24956
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Modified Expanded Graphite and Zinc Borate on the Flammability, Thermal Stability and Crystallization Behavior of LLDPE/EVA Composites with Mg(OH)2/Al(OH)3

Abstract: In this work, modified expandable graphite (MEG) and zinc borate (ZB) are melt-blended with metal hydroxide/aluminum hydroxide flame retardant linear lowdensity polyethylene/ethylene vinyl acetate (LLDPE/ EVA) blends. The synergistic effects of MEG with ZB on the flammability, thermal stability and crystallization behaviors of LLDPE/EVA composites are characterized and discussed by UL-94 vertical burning, limiting oxygen index (LOI), thermogravimetric analysis, cone calorimeter test (CCT), carbon layer morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…The narrowing of the crystallinity peak by increasing the nanoparticle percentage means that the size distribution of the formed crystals has decreased. [42] Improved Avrami equation was fitted on crystallization data to study the kinetics of crystallization: where χ t is the crystallinity ratio, Z t is a growth rate constant, nis the Avrami index and C is cooling rate. The parameters could be determined by fittinglntvs ln(−ln[1 − χ t ]).…”
Section: F I G U R E 7 a Heating Thermograms Of The Samples Andb mentioning
confidence: 99%
“…The narrowing of the crystallinity peak by increasing the nanoparticle percentage means that the size distribution of the formed crystals has decreased. [42] Improved Avrami equation was fitted on crystallization data to study the kinetics of crystallization: where χ t is the crystallinity ratio, Z t is a growth rate constant, nis the Avrami index and C is cooling rate. The parameters could be determined by fittinglntvs ln(−ln[1 − χ t ]).…”
Section: F I G U R E 7 a Heating Thermograms Of The Samples Andb mentioning
confidence: 99%
“…Expandable graphite (EG) is a novel type of intumescent flame retardant. Due to its excellent flame retardancy, EG has been used for many times in flame‐retardant polyolefins, 19–21 poly(methyl methacrylate), epoxy resin, 22 and polyurethane (PU) 23–25 . When EG is heated to about 200°C, EG expands rapidly and becomes a swollen and multi‐voided “worm‐like” structure, resulting in a large amount of charred residue covering the polymer surface 26 .…”
Section: Introductionmentioning
confidence: 99%
“…A reasonable yet well‐accepted approach to solve this problem is to incorporate flame‐retardant additives to improve flame retardancy and anti‐dripping properties of EVA 8,12,13 . In recent years, a wide variety of flame retardant additives have been examined in EVA among which are mineral components (zinc borate, 14–18 magnesium hydroxide, 16,19,20 aluminium hydroxide 16,21,22 ), phosphorus‐based materials (red phosphorus, 23,24 ammonium polyphosphate (APP), 7,22,25–27 nitrogen‐based systems (melamine 28,29 ), and carbon‐based flame retardants (expandable graphite [EG], 30–33 graphene nanoplatelets, 34–36 and graphene oxide 30,37 ). Overall, it has been demonstrated that carbon‐based materials such as graphene can change the pyrolysis pathway, dripping, and thermal conductivity in polymer systems 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al 52 used hybrid FR of EG (20 wt.%) and phosphonium sulfonates (2.5 wt.%) and achieved V‐0 in UL‐94, and both pHRR and THR dropped significantly at such loading level. Some other complex systems with synergistic effects like modified EG with blend of metal hydroxide and zinc precursors are examined in EVA 16 . In a previous work, 53 we developed FR additive by grafting APP onto exfoliated graphene platelets (GNP‐g‐APP).…”
Section: Introductionmentioning
confidence: 99%